Bimekizumab in patients with psoriatic arthritis, naive to biologic treatment: a randomised, double-blind, placebo-controlled, phase 3 trial (BE OPTIMAL). Issue 10370 (7th January 2023) - McInnes, Iain B; Asahina, Akihiko; Coates, Laura C; Landewé, Robert; Merola, Joseph F; Ritchlin, Christopher T; Tanaka, Yoshiya; Gossec, Laure; Gottlieb, Alice B; Warren, Richard B; Ink, Barbara; Assudani, Deepak; et al.
Summary: Background: Bimekizumab is a monoclonal IgG1 antibody that selectively inhibits interleukin (IL)-17A and IL-17F. We assessed the efficacy and safety of bimekizumab in patients with active psoriatic arthritis who were naive to biologic disease-modifying antirheumatic drugs (DMARDs). Methods: BE OPTIMAL was a 52-week, phase 3, multicentre, randomised, double-blind, placebo-controlled, active reference (adalimumab) trial done at 135 sites (hospitals, clinics, doctors' offices, and research centres) in 14 countries. Eligible patients were 18 years or older with a documented diagnosis of adult-onset psoriatic arthritis that met the Classification Criteria for Psoriatic Arthritis for at least 6 months before screening. Participants were randomly assigned with an interactive-voice and web-response system on the basis of a predetermined randomisation schedule (3:2:1, stratified by region and bone erosion number at baseline) to bimekizumab 160 mg every 4 weeks, placebo every 2 weeks, or the reference group (adalimumab 40 mg every 2 weeks), all administered subcutaneously. At week 16, patients randomly assigned to placebo switched to bimekizumab 160 mg every 4 weeks. The primary endpoint was the proportion of patients reaching 50% or greater improvement in American College of Rheumatology criteria (ACR50) at week 16 (non-responder imputation). Efficacy analyses included all patients who were randomly assigned (intention-to-treat population); the safety analysis set comprised patients who received one or more doses of treatment. Data are presented to week 24 (preplanned analysis). This trial is registered at ClinicalTrials.gov, NCT03895203 . Findings: Between April 3, 2019, and Oct 25, 2021, 1163 patients were screened and 852 were randomly assigned to bimekizumab (n=431), placebo (n=281), and reference (adalimumab; n=140) groups. At week 16, significantly more patients receiving bimekizumab (189 [44%] of 431) reached ACR50 response versus placebo (28 [10%] of 281; odds ratio 7·1 [95% CI 4·6–10·9], p<0·0001; adalimumab 64 [46%] of 140). All secondary hierarchical endpoints were met. Treatment-emergent adverse events up to week 16 were reported in 258 [60%] of 431 patients receiving bimekizumab, 139 [49%] of 281 patients receiving placebo, and 83 [59%] of 140 patients receiving adalimumab. No deaths occurred. Interpretation: Bimekizumab treatment had superior improvements in joint, skin, and radiographic efficacy outcomes at week 16 compared with placebo in patients with psoriatic arthritis who were naive to biologic DMARDs. The safety profile of bimekizumab, including the occurrence of fungal infections, was consistent with previous phase 3 studies in patients with plaque psoriasis, and with IL-17A inhibitors. Funding: UCB Pharma.